Various types of exercises for studying english for children - Lunina, K. O. (ХНУРЕ, 2021)
It is not news that studying English is very important nowadays. There are 400 million native speakers of this language on the planet and English is the official or one of the main languages of communication in more than 50 countries. Knowing this language there will be opened millions of various possibilities in each sphere of human activity such as design, IT, medicine, engineering, economics and many others. English will help to build a successful career and bring positive emotions to a person's life. And the best way of studying English begins from childhood when everything is given with ease.
Keywords: Information; English